Model Komunikasi Organisasi Pemberdayaan Kesejahteraan Keluarga (PKK) Dalam Mengimplementasikan Program Bank Sampah Duren - Jannah, Nida Aisahtul; Yuniani, Hani; Meliala, Robbikal Muntaha (CV. ITTC INDONESIA, 2024)
The organizational communication model functions as a tool to ensure that communication is on target in accordance with the objectives of the PKK RT 08 Kampung Padurenan organization, namely to advance the environment by facilitating the community in managing waste banks. This study aims to determine the Organizational Communication Model (PKK) in Implementing the Duren Waste Bank Program. The organizational communication model in this study uses the Stimulus-Response model and the Aristotle model with upward, downward and sideways communication directions. Flor's environmental communication theory is used to complement the organizational communication model. The research method used is descriptive qualitative. Data collection techniques include interviews, observations, documentation and literature studies. The results of this study indicate that the organizational communication model carried out by the PKK RT 08 organization in implementing the Duren Waste Bank was declared successful. This can be seen from a clear understanding of communication so that it can be ensured that all organizations involved understand what is being said. This Organizational Communication Process can also be declared unsuccessful due to the lack of active participation in communication from the head of the waste bank in each of his work program activities, so that members often feel that leaders can only give orders without giving examples.